Literature Review: Studi Komparatif Parameter Standarisasi Spesifik dan Non-Spesifik Simplisia Buah Unggulan Indonesia - Siti Haura Khairunnisa; Albertrysia Richzchika Yolanurnazwa; Neng Nely Widianti Rahma; Perdi ansyah; Yonathan Tri Atmodjo Reubun (Jurnal Ayurveda Medistra, 2026)
As a megabiodiversity country, Indonesia possesses a wealth of local fruits with extensive pharmacologicalpotential; however, systematic comparative studies of standardization parameters for fruit crude drugs remainvery limited. This literature review aims to compile a comparative study of specific and non-specificstandardization parameters for ten leading Indonesian fruit crude drugs based on scientific literature and toevaluate their compliance with the Indonesian Herbal Pharmacopoeia (FHI). A systematic literature search wasconducted via Google Scholar using the keywords “standardization of fruit crude drugs,” “specific and non-specific parameters,” and “characterization of crude drugs.” A total of 9 journal articles and 1 thesis publishedbetween 2017 and 2025 met the inclusion criteria and were analyzed comparatively. The study covered tentypes of fruit, namely green apples, hiyung chili peppers, yellow squash, red pomegranates, ceremai, belimbingwuluh, asam gelugur, lime, limpasu, and selutui puka. Specific parameters revealed characteristic organolepticvariations as well as significant differences in water-soluble extract content (3.6–65.57%) and ethanol-solubleextract content (3.9–70.50%). Non-specific parameters identified three critical safety issues: the acid-insolubleash content (KATLA) of green apples exceeded the Indonesian Food and Drug Administration (BPOM RI) limit(6.95%); Cadmium contamination in Hiyung chili peppers exceeded the maximum limit (4.00 mg/kg vs. 0.3mg/kg); and the KATLA content in Ceremai (1.50–1.59%) exceeded BPOM RI requirements. None of the crudedrugs or extracts comprehensively met all FHI requirements. Standardization of extraction procedures, morecomprehensive parameter testing, and the development of specific FHI monographs for undocumentedIndonesian fruit crude drugs are required.Keywords: Standardization of fruit crude extracts, specific parameters, non-specific parameters, characterization of crude extracts.